Designing Pictures Story Book Using Cultural Language Learning Approach (CLLA) to Improve English Skills - Nurul Fatma; Sujito (Journal of Islamic Studies and Education, 2025)
This study aimed to develop a Picture Story Book (PSB) to enhance English proficiency among elementary learners and to identify appropriate teaching materials. The research employed a Research and Development (R&D) approach, structured using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected through observations, interviews, and questionnaires during the needs analysis phase. The English material, titled "Let’s Have Fun with Picture Story Book (PSB)," was developed based on the 2013 national curriculum, integrating character education and communicative language learning. Validation was conducted through focus group discussions (FGD) with English teachers and caretakers using Likert scale questionnaires. The final product comprised six thematic units. Evaluation of learning outcomes, based on pre-test and post-test analysis, showed a significant improvement in student performance from a mean pre-test score of 52.3 to a post-test score of 75.8. These results affirm the PSB’s effectiveness and appropriateness for supporting English instruction in elementary education at MIM PK Kartasura.